Basketball referee's gaze behavior and stimulus selection in relation to visual angle perspective and officiating mechanics and expertise - Ruiz, A. J.; Albaladedejo, C.; Reina, R.; Moreno, F. J. (European Journal of Human Movement, 2023)
This work aimed to describe the visual search behavior of basketball referees. Eight national and eight regional basketball referees took part in the study. The participants watched five projected gameplay video clips twice from different perspectives: lead and trail referee positions. Dependent variables were based on the extrinsic ocular motility (number of fixations, average fixation time, and total fixation time on the selected areas of interest), and the independent variables were expertise (expert vs novice) and visual angle (lead vs trail referee position). Most gaze behavior differences were found between the lead and trail positions (total fixation time: F = 10.79; p < 0.01; ?p² = 0.435; average fixation time: F = 16.23; p < 0.01; ?p² = 0.537). It was found that basketball referees mainly follow a target strategy on the attacking player with the ball and a visual pivot on the players' trunk. Expertise does not determine the number or time of fixations, but it does influence fixation location.